2020
DOI: 10.3390/ani10112124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Stress on Dairy Cow Performance and on Expression of Protein Metabolism Genes in Mammary Cells

Abstract: The aim of this study was to assess the effect of heat stress on dairy cow performance and on the expression of selected genes involved in milk protein metabolism. Eight Italian Holstein Friesian cows were kept under thermoneutral conditions (temperature–humidity index (THI) < 72, CON) for 8 days and under mild heat stress conditions (72 < THI < 78, HS) for an additional 8 days. The rectal temperature, feed intake, and milk yield were recorded during the last 3 days of the CON and HS periods. During t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 53 publications
2
10
0
Order By: Relevance
“…The discrepancy may be attributed to the differed timing of mammary biopsies. However, our findings are in accordance with Corazzin et al [ 38 ], who reported similar levels of CSN2 in milk somatic cells (representative of mammary tissue) of lactating cows exposed to thermoneutral conditions and then mild heat stress.…”
Section: Discussionsupporting
confidence: 93%
“…The discrepancy may be attributed to the differed timing of mammary biopsies. However, our findings are in accordance with Corazzin et al [ 38 ], who reported similar levels of CSN2 in milk somatic cells (representative of mammary tissue) of lactating cows exposed to thermoneutral conditions and then mild heat stress.…”
Section: Discussionsupporting
confidence: 93%
“…However, in our study, milk fat increased in summer, which may have been caused by long-term HS, leading to the decomposition of long-chain fatty acids, and thus, increased milk fat. Furthermore, the higher percentage of fat in the milk of heat stressed cows could be attributed to the reduction in milk yield and subsequent concentration of fat, in addition to possibly greater non-protein nitrogen contents in the milk produced from cows under HS [ 26 ]. Several studies have shown that milk protein and lactose concentrations are higher during the first parity than the third parity [ 24 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only if the values of the environment are at the optimal level (usually recommended temperature within a range of −0.5 to 20.0 °C and 40–80% relative humidity), the dairy cows are in a state of well-being [ 8 , 9 , 10 , 11 ]. The results of some research studies revealed that even mild heat stress reduced the feed intake and milk yield of dairy cows [ 12 , 13 ]. The influence of temperature conditions in the hot tropical climate on milk production is very strong and causes serious problems, especially for dairy cows with high milk yield [ 14 ].…”
Section: Introductionmentioning
confidence: 99%